Maximum window-to-wall ratio of a thermally autonomous building as a function of envelope U-value and ambient temperature amplitude. (15th May 2015) - Ma, Peizheng; Wang, Lin-Shu; Guo, Nianhua
Abstract : Graphical abstract: Highlights: Investigated the max WWR as a function of envelope U -value and ambient T amplitude. Obtained the max WWR of seven US cities using the conclusions of this investigation. Point out good envelope is more important in locations with large ambient T amplitude. Abstract: In two earlier papers we proposed a process assumption - based design method, one aim of which is the determination of the thermal requirement of a building by investigating the building functioning as a dynamic thermal system. The principal constraint of that determination is the building indoor temperature range to be no more than 2 °C. In this paper we focus on the thermal requirement of maximum WWR (window-to-wall ratio) allowed by the constraint as a function of envelope U -value and ambient temperature amplitude. Seven US cities are studied to represent a range of ambient temperature amplitudes. As the window part of a building's envelope is a prominent architectural feature of the building, WWR and its allowed maximum in terms of thermal autonomy are the signature/reflection of local ambient temperature amplitude and the variety of envelopes of building stock in each locality. Such signal characteristics are otherwise referred to as regional architecture.